Survival after neoadjuvant/induction combination immunotherapy vs combination platinum‐based chemotherapy for locally advanced (Stage III) urothelial cancer. Issue 11 (10th June 2022) - Einerhand, Sarah M. H.; van Dijk, Nick; van Dorp, Jeroen; de Feijter, Jeantine M.; van Montfoort, Maurits L.; van de Kamp, Maaike W.; Schaake, Eva E.; Boellaard, Thierry N.; Hendricksen, Kees; van der Heijden, Michiel S.; van Rhijn, Bas W. G.
Abstract: Despite treatment with cisplatin‐based chemotherapy and surgical resection, clinical outcomes of patients with locally advanced urothelial carcinoma (UC) remain poor. We compared neoadjuvant/induction platinum‐based combination chemotherapy (NAIC) with combination immune checkpoint inhibition (cICI). We identified 602 patients who attended our outpatient bladder cancer clinic in 2018 to 2019. Patients were included if they received NAIC or cICI for cT3‐4aN0M0 or cT1‐4aN1‐3M0 UC. NAIC consisted of cisplatin‐based chemotherapy or gemcitabine‐carboplatin in case of cisplatin‐ineligibility. A subset of patients (cisplatin‐ineligibility or refusal of NAIC) received ipilimumab plus nivolumab in the NABUCCO‐trial (NCT03387761). Treatments were compared using the log‐rank test and propensity score‐weighted Cox regression models. We included 107 Stage III UC patients treated with NAIC (n = 83) or cICI (n = 24). NAIC was discontinued in 11 patients due to progression (n = 6; 7%) or toxicity (n = 5; 6%), while cICI was discontinued in 6 patients (25%) after 2 cycles due to toxicity ( P  = .205). After NAIC, patients had surgical resection (n = 50; 60%), chemoradiation (n = 26; 30%), or no consolidating treatment due to progression (n = 5; 6%) or toxicity (n = 2; 2%). After cICI, all patients underwent resection. After resection (n = 74), complete pathological response (ypT0N0) was achieved in 11 (22%) NAIC‐patients and 11 (46%) cICI‐patients ( P  = .056). Median (IQR) follow‐up was 26 (20‐32) months. cICI was associated with superior progression‐free survival ( P  = .003) and overall survival ( P  = .003) compared to NAIC. Our study showed superior survival in Stage III UC patients pretreated with cICI if compared to NAIC. Our findings provide a strong rationale for validation of cICI for locally advanced UC in a comparative phase‐3 trial. Abstract : What's new? Single‐arm trials have shown promising results for the treatment of urothelial carcinoma by neoadjuvant immune checkpoint inhibition (ICI). Our study in Stage III urothelial carcinoma building upon the NABUCCO trial is the first to compare clinical outcomes between standard platinum‐based combination neoadjuvant/induction chemotherapy (NAIC) and ICI combining ipilimumab and nivolumab. Pathological response rates were higher in patients treated with combination ICI, which was also associated with superior survival compared to NAIC. The findings provide a compelling rationale for the validation of preoperative combination ICI for Stage III urothelial carcinoma in a comparative phase‐3 study.